Determining the Applicable Law on Privileges in International Commercial Arbitration - Kocev, Ljuben (Iustinianus Primus Law Review, 2018)
International arbitration is rapidly becoming a preferred method for dispute settlement between commercial entities and is replacing the traditional methods of resolving disputes in front of state courts. As such, international arbitration develops in its own pace, slowly creating coherent rules suitable for efficient settlement of the complex disputes brought in front of the arbitral tribunals. Although there are a large number of specific practices that have emerged throughout the years, the question of privileges might be one of the last few issues that remain unresolved to this date. Parties increasingly rely and invoke privileges in proceedings to avail themselves from having to disclose certain documents, when faced with a request for document production from the opposite side. When raising privileges, parties will generally expect that the nature and the scope of privileges will be based on their domestic legal system. This reliance and expectation in fact represents the root of the problems that arise, since not all countries treat privileges in the same manner. Currently there is lack of guidance that would aid arbitrators in dealing with this issue and in determining the applicable law. In this paper we are going to give a brief introduction of privileges, defining the concept of privileges; the types of privileges that exist and which are most likely to arise in international arbitration and focus on the methods for determining the applicable law for privileges. At the end, we are going to propose a method which we believe would be most suitable for determining the applicable law on privileges and which would pave the way for uniform approach in dealing with privileges in the future.
Keywords: international arbitration, privileges, IBA Rules, legal advice privilege, settlement discussion privilege